Elastic moduli of a Brownian colloidal glass former. (11th December 2017) - Fritschi, S; Fuchs, M
Abstract: The static, dynamic and flow-dependent shear moduli of a binary mixture of Brownian hard disks are studied by an event-driven molecular dynamics simulation. Thereby, the emergence of rigidity close to the glass transition encoded in the static shear modulus G ∞ is accessed by three methods. Results from shear stress auto-correlation functions, elastic dispersion relations, and the elastic response to strain deformations upon the start-up of shear flow are compared. This enables one to sample the time-dependent shear modulus G ( t ) consistently over several decades in time. By that a very precise specification of the glass transition point and of G ∞ is feasible. Predictions by mode coupling theory of a finite shear modulus at the glass transition, of α -scaling in fluid states close to the transition, and of shear induced decay in yielding glass states are tested and broadly verified.